Imidacloprid exposure in rats induces cardiac inflammatory response through activating TLR4/NF-κB/NLRP3 and JAK/STAT signaling pathways: focus on the berberine-loaded nanoliposomes - Alkharashi, Layla; Farag, Amina A.; Gamil, Noha M.; Mahran, Yasmen F.; Badr, Amira M.; Bayoumi, Heba; Mostafa, Mahmoud; Binmughram, Awatif A.; Alquhayz, Aljawharah F.; BinObaid, Gadah M.; Bayoumy, Nervana M.; Elwakeel, Eman E.; et al. (Frontiers in Toxicology, 2026)
The neonicotinoid insecticide, imidacloprid (IMI), is one of the widely used pesticides with well-documented serious health effects that are noticeable with long-term exposure. However, the long-term effects of IMI on cardiac tissues have not been fully elucidated. Herein, we investigated the mechanisms of IMI-induced cardiotoxicity. Additionally, we examined the potential protective effects of the natural alkaloid, berberine (BBR), against IMI-induced cardiotoxicity. Rats received IMI (45 mg/kg/day, orally) for 30 days, alone or in combination with BBR-loaded liposomes (BBR-Lip) at a dose of 10 mg/kg, intraperitoneally. Cardiac troponin I (cTnI), creatine kinase-MB (CK-MB), oxidative stress, inflammatory markers, and histopathological alterations were assessed. IMI caused significant cardiac damage as shown by increased levels of cTnI and CK-MB and histopathological insults examined by H and E and transmission electron microscopy. These changes were accompanied by the induction of oxidative stress and inflammatory markers. Additionally, IMI inhibited the expression of Nrf2, a powerful regulator of cellular antioxidant defense and activated inflammatory pathways by inducing expressions of TLR-4, NF-κB, NLRP3-inflammasome and gasdermin. Moreover, IMI induced cardiac expressions of TGF-β, p-JAK, and p-STAT, which worsens the oxidative stress and inflammatory status. Co-administration of BBR-Lip attenuated the biochemical, histological and molecular dysregulation induced by IMI in cardiac tissues. Collectively, this study provides mechanistic insights into the cardiotoxic effects of IMI as well as the potential protective effects of BBR-Lip.